Sosialisasi Peningkatan Pengetahuan dan Kesadaran Siswa dalam Pemilahan Sampah Berdasarkan Jenisnya di SMP Al-Azhar Medan - Harahap, Anggi Novita Sari; Rifdha, Aliyah Rifdha; Yuwanda, Febby Yuwanda; Prananda, Anasya Prananda; Muliyani; Pasaribu, Natasha Melfisyaira; Hasiah, Nursyahidah; Sabina, Ramania Sabina; Siti Fanisa (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Waste management must be done properly because waste is very dangerous for human health and the surrounding environment. Waste recycling must be done properly so that environmental pollution does not occur that can interfere with human health. The purpose of this study is to provide health education regarding waste sorting/management around schools for students of Al-Azhar Medan Junior High School. The research model in this study is the One Group Pre-test Post-test where the dependent variables are measured as one group before (pre-test) and after (post-test) treatment is given. The results showed that there were significant changes in participants' pre-test and post-test scores, namely pre-test score data had an average (mean) increase of 7.7, and post-test score data had an average increase of 8.9. These changes show that students experience an increase in knowledge after participating in education or material about waste sorting.